Violência doméstica contra as mulheres nas relações íntimas de afeto : influências das estratégias de coping e impacto no bem-estar subjetivo - Côrtes, Vanessa Araujo Souza (2014)
The violence is a phenomenon essentially built on social. It is complex, controversial and multifaceted, encompassing all cultures in their different social plots, either in public or private levels. A violence that affects primarily private levels is domestic violence, especially against women. This can be defined as an act of violence (action or omission), which is based on the gender issue and that may have biopsychosocial consequences. This type of violence is recognized by the World Health Organization as a matter of health and social mainly for being characterized as a manifestation of power relations and historical culturally dissimilar, favoring the dominance of men over women. In recent years, however, with the release of the Maria da Penha Law (L. 11340), there was an increase in the number of reported cases and reported in the media of women who suffer violence or who have been killed as a result of this. However, these rates still aren´t consistent with the serious reality, because for various reasons many women remain silent and submissive, configured as a chronic problem. This work aims to investigate the influence of different coping strategies in order to experience the situation of domestic violence in intimate relationships of affection and evaluate the impact of this violence on subjective well-being of women victims. For this, multimethod research approach (qualitative and quantitative) was performed with cross-sectional survey type. The sample consisted of 486 women victims of Sergipe (49.3 %) and not the victims (50.6 %) of domestic violence in intimate relationships of affection, who accessed the WPS and Reference Centres for Social Assistance. As for the instrument consisted of a questionnaire crawler (containing questions about sociodemographic data and open questions about domestic violence) and three scales: World Health Organization Violence Against Women (WHO VAW), Subjective Well-Being Scale (EBE) and Modes of Coping Scale (EMEP). The descriptive results of the demographic data comparing the two groups (women victims rather than victims), including analysis of the questionnaire tracker and analysis of the scales WHO VAW, EBE and EMEP. The results showed that subjective well-being is higher in women than non-victims of violence and the coping strategies caused a little impact on the relationship between domestic violence against women in intimate relationships of affection and subjective well -being.